Status and Journey of Financial Inclusion in India - Kirti (Research Parks Publishers, 2022)
Inequality and exclusion are the two biggest problems of economy and world. The roots of these problems are gone very deep. So to eradicate the problems of exclusion, inclusion growth is so much necessary. Many researchers have realized that the problems of exclusion create obstacles in the path of inclusion. Thus the inclusive growth is mandatory for the sustainable growth and development of economy. Providing opportunities for every person for improving his standard of living is necessary for a developing and prosperous economy and country. People’s growth is possible when they are connected with vital networks of modern economy. Many people, especially women, still lack access to financial services as well as financial literacy, which is a key for social inclusion. Financial access means access to a full suite of financial services provided with quality for everyone who can use financial services. It is necessary that every person understand the importance of financial inclusion. It is necessary to understand that the key ingredient of inclusion is financial inclusion. Inclusive growth refers to both pace and pattern of economic growth. Financial inclusion means to provide sustainable, affordable, safe, accessible life to human being with the help of a tool which is called finance. It helps in mobilizing the saving of person, make money from money, taking affordable loans, deposit money into banks, taking insurance for protecting their own lives and their families. Thus in this paper my main emphasis on the financial inclusion and economic growth.